Pengembangan Buku Ajar Desain Pembelajaran Biologi Berbasis Socio-Eco-Techno-Preneurship: (Development of Socio-Eco-Techno-Preneurship Based Biology Learning Design Textbook) - Nasrul Hakim; Dwi Kurnia Hayati; Umi Saputri (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This study aims to develop a socio-eco-techno-preneurship-based Biology Learning Design textbook. The development model used in this research is a 4D development model which includes Define, Design, Develop, and Disseminate. The results of the design expert validation obtained a score of 89% included in the very good category. The results of material expert validation obtained a score of 92% of and included in the very good category. The validation of linguists obtained a score of 90% and included in the very good category. The results of the response from the Tadris biology lecturer obtained a score of 85% and included in the very good category. The results of the limited trial to biology tadris students obtained a score of 87.25% and included in the very good category. Based on the research data, it can be concluded that the textbook product developed is suitable for use in the learning process. Key words: Learning Design, Texbook, entrepneurship Â ABSTRAK Penelitian ini bertujuan untuk mengembangkan buku ajar Desain Pembelajaran Biologi berbasis socio-eco-techno-preneurship. Model pengembangan yang digunakan dalam penelitian ini adalah model pengembangan 4 D yang meliputi Define, Design, Develop, dan Disseminate. Hasil validasi ahli materi diperoleh skor 90% sebesar dan termasuk dalam kategori sangat baik . Hasil validasi ahli desain diperoleh skor 89% termasuk dalam kategori sangat baik. Validasi ahli bahasa diperoleh skor 92% dan termasuk kategori sangat baik. Hasil respon dosen Tadris biologi diperoleh skor 87,5% dan termasuk kategori sangat baik. Hasil ujicoba terbatas kepada mahasiswa tadris biologi diperoleh skor 90% dan termasuk kategori sangat baik. Berdsarkan data hasil penelitian dapat disimpulkan produk buku ajar yang dikembangkan layak digunakan dalam proses pembelajaran.Â Kata kunci: Desain Pembelajaran, Buku Ajar, entrepreneurship